Arduino and LEGO projects - Lazar, Jon (Apress Imprint: Apress, 2013)
We all know how awesome LEGO is, and more and more people are discovering how many amazing things you can do with Arduino. In Arduino and LEGO Projects, Jon Lazar shows you how to combine two of the coolest things on the planet to make fun gadgets like a Magic Lantern RF reader, a sensor-enabled LEGO music box, and even an Arduino-controlled LEGO train set. Learn that SNOT is actually cool (it means Studs Not on Top) See detailed explanations and images of how everything fits together Learn how Arduino fits into each project, including code and explanations Whether you want to impress your friends, annoy the cat, or just kick back and bask in the awesomeness of your creations, Arduino and LEGO Projects shows you just what you need and how to put it all together.